2020
DOI: 10.1515/psych-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Approach, Avoidance, and the Perception of Credibility

Abstract: Based on a functional approach to credibility judgments, the authors hypothesize that receivers’ judgments of senders’ credibility involve an evaluative dimension (i.e., good–bad) and are associated with approach and avoidance tendencies. In three experiments (total N = 645), participants (receivers) judged the credibility of suspects (senders) denying involvement in a mock theft. While watching or reading the message, receivers performed an approach-related (arm flexion) or an avoidance-related (arm extension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Because of all these reasons, it has been suggested that whenever several experiments examining the same phenomenon are reported in a paper, a final single‐paper meta‐analysis should be the default statistical procedure to integrate the results (McShane & Böckenholt, 2017). Indeed, some recent articles in our field include a meta‐analysis of the separate studies at the end (e.g., Ask, Calderon, Mac Giolla, & Reinhard, 2020; Street & Masip, 2015). We examined whether the meta‐analytical integration of our two experiments would support Hypotheses 1, 2a, and 2b.…”
Section: Meta‐analytical Integration Of Experiments 1 Andmentioning
confidence: 99%
“…Because of all these reasons, it has been suggested that whenever several experiments examining the same phenomenon are reported in a paper, a final single‐paper meta‐analysis should be the default statistical procedure to integrate the results (McShane & Böckenholt, 2017). Indeed, some recent articles in our field include a meta‐analysis of the separate studies at the end (e.g., Ask, Calderon, Mac Giolla, & Reinhard, 2020; Street & Masip, 2015). We examined whether the meta‐analytical integration of our two experiments would support Hypotheses 1, 2a, and 2b.…”
Section: Meta‐analytical Integration Of Experiments 1 Andmentioning
confidence: 99%